Decrease in beneficial bacteria and increase in harmful bacteria in Gastrodia seedlings and their surrounding soil are mainly responsible for degradation of Gastrodia asexual propagation - Wang, Xi; Gao, Yugang; Zang, Pu; Zhang, Ge; Yang, Xinyu; Liu, Qun (Frontiers in Plant Science, 2024)
To clarify the causes of the degradation of asexual reproduction Gastrodia elata Bl. f. glauca S. chow (GeB)seedlings and find ways to relieve their degradation, we analyzed the types and quantities of GeB seedlings and surrounding soil microorganisms in 1st to 3rd generations of asexual reproduction, isolated and identified the dominant strains of GeB in the 1st to 3rd generations and screened the antagonistic bacteria of its pathogenic fungi, and evaluated the effects of beneficial bacteria on the production performance of seedlings planted with GeB. With an increase in the number of asexual reproductive generations, the number of pathogenic fungi and bacteria in GeB and the surrounding soil increased, and the number of beneficial fungi and bacteria decreased. Pseudomonas sp., Agrobacterium rhizomes, and Herbaspirillum hiltneri were isolated and identified in the 1st generation, and Trichoderma harzianum, Penicillium viridiatum, Fusarium oxysporum, and Novosphingobium sp. were isolated and identified in the 3rd generation.Antagonistic strains of the three pathogenic bacterial strains were screened. In conclusion, beneficial bacteria significantly improved the production performance of asexual reproductive seedlings planted with GeB.